Rodents and Restionaceae : sex-specific plant-animal interactions in dioecious plants - Van Blerk, Justin (Department of Biological Sciences, 2016)
Differing plant canopy structures between the sexes of the dioecious Cannomois congesta (Restionaceae) were found to be the result of the destructive pre-dispersal seed predation methods used by the four-striped grass mouse (Rhabdomys). Mature, reproductive culms on female plants were felled down (mid way along the culm) in large numbers by Rhabdomys in order for it to access the seeds held terminally on culms. Male plants were largely unaffected due to their lack of seeds. Seeds acquired through culm-felling by Rhabdomys were all eaten shortly after their discovery, leading to significant seed mortality each year and reducing the rate of seed dispersal by ants (myrmecochory). I studied the physiological effects of culm-felling by Rhabdomys in C. congesta. Firstly I investigated nutrient resorption from senescing culms and considered the effects of reproductive effort (higher in females) and sex-specific nutrient losses. I found that nutrient resorption from mature culms was highly efficient in both sexes. Culm-felling by Rhabdomys lead to the loss of pre-senescent culm tissue in females and therefore lead to the loss of a significant proportion of potentially resorbed nutrients. Nutrient resorption was found not to be flexible as a strategy to compensate for higher reproductive costs/nutrient-losses in females. This was possibly due to nutrient resorption occurring near is physiological maximum. Plant photosynthetic performance was also investigated using stable isotopes and gas exchange and was found to be similar in both C. congesta sexes throughout the year. The influence of culm-felling by Rhabdomys on female micro-climate also did not appear to have a significant influence on photosynthetic performance between sexes. There was a general lack of evidence to suggest compensatory physiological changes or reductions in fitness (photosynthetic capacity/growth/reproduction) in females due to higher reproductive costs/nutrient-losses. The lack of physiological differences and the fact that females supported a greater number of culms relative to males suggested that other compensatory mechanisms could exist. Phenological differences were discovered and could be important in allowing flexibility between sexes to best use available resources for their specific sexual requirements. Another possibility is that compensatory growth occurred in females at the cost of rhizome-stored nutrients. This has been shown to occur in graminoids after high levels of herbivory (Bryant et al 1983).